PERSEPSI MASYARAKAT TANI TERHADAP PROGRAM PEMBERDAYAAN PETANI MELALUI SOSIALISASI TANAMAN OBAT Artemisia annua L. DI KABUPATEN KEPAHIANG PROVINSI BENGKULU - Andani, Apri; Harini Bertham, Yudhy; Dipo Nusantara, Abimanyu (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2014)
The purpose of this study is to determine the level of farmers’ perception towards empowerment program of farmers through public introduction of Artemisia annua L. medicinal plants in Kepahiang District Bengkulu Province. The location is intentionally determined by considering the geographical eligibility factor for the growth and development of the plant Artemisia annua L., which is more than 1000 meters above sea level. The study is conducted in three villages; Bandung Baru, Tangsi Duren, and Sukasari. In this study, respondents are deliberately determined on the farmers’ willingness to participate in the dissemination program of the research results about the commodities. Data were analyzed using qualitative descriptive method using ordinal scale with scores to distinguish the response of the respondents to the question or statement. The results show that knowledge of farming communities has improved about Artemisia annua L. plants; previously they did not know at all about this plant. Besides being suitable for agro-climate, they also feel that the plant has benefited the family’s health, although not directly felt economically. Generally, the farmers are willing to inform others, join and participate in the process of Artemisia annua L. cultivation. Keywords: Perception, Empowerment, Medicinal Plants, Artemisia annua L